Kipiyecipakiciipe (“coming home”): a study protocol for a multi-method investigation of culturally grounded resilience against substance-use among Shawnee adults - White, Evan J.; Tomm, Ryan; O'Keefe, Victoria M.; Bethel, Danielle L.; Cochran, Gabe; Torres, Makiah; Grubin, Fiona; Conrad, Maisie; Baughman, Nicole R.; Wiglesworth, Andrea; Ren, Xi; Vaught, Wesley (Frontiers in Public Health, 2025)
BackgroundAmerican Indian and Alaska Native (AI/AN) peoples bear the highest U.S. burden of substance-use disorder (SUD) and drug-overdose mortality. Mechanistic evidence linking community-defined cultural protective factors to neurobehavioral pathways of SUD risk is virtually absent. Most AI/AN health studies are descriptive and rarely integrate neuroscience.ObjectivesThe Kipiyecipakiciipe (“coming home”) project aims to (i) operationalize Shawnee-defined cultural engagement variables, (ii) test their associations with neurobehavioral markers of reward, decision-making, and self-regulation, and (iii) establish evidence base for tribally guided prevention and recovery strategies.MethodsGuided by community-based participatory research, the three-phase multi-method protocol combines qualitative inquiry, a Community Readiness Assessment (CRA), and multimodal neuroimaging. Phase 1 included 22 Shawnee adults and employed N = 3 focus-group discussions (including Nominal Group Technique) and N = 1 in-depth interview to generate an operational lexicon of cultural protective factors and to adapt a Community Needs Assessment (CNA). Phase 2 enrolls 90 Shawnee adults in a simultaneous functional MRI/electro-encephalography (fMRI/EEG) battery comprising culturally tailored picture and audio paradigms, a Monetary Incentive Delay (MID) task, a three-arm bandit task, and the Horizon exploration task. Self-report scales assess cultural identity, mental health, substance use, impulsivity, and risk. Parallel CRA interviews (n = 12) quantify community readiness for SUD interventions across six dimensions. Phase 3 will recruit Shawnee citizens with lived SUD experience to examine whether cultural, behavioral, and neural markers predict recovery-related outcomes (e.g., craving, self-efficacy).DiscussionBy integrating community insight with state-of-the-art neuroimaging under Tribal governance, this protocol addresses critical knowledge gaps in Indigenous SUD research, models CARE-aligned data stewardship and establishes a transferable framework for culturally grounded precision substance use prevention.